(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article talks about the realization of artistic psychologism in today’s modern Uzbek prose and the artistic charm and unique aspects of the works of the talented artist Nazar Eshonqul, who has been making a great contribution to its development. In his works, the vivid expression of artistic psychology and the peculiarities of the characters of the heroes of the work are mentioned.